Dampak Harmonisa yang ditimbulkan 0leh Beban Lampu Flourecent pada Instalasi Listrik - Tri Artono -; Junaidi Asrul -; Efendi - -; Rahmi Berlianti - (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2017)
The problem of harmonics in electric power system can not be ignored, because with the increasing use of non-linear equipment (eg flouresent lamp), that flouresent lamp can cause harmonics in odd order of multiples of 3 that is equal to 15% , in this research two measurements are measured by using flouresent lamp load and incandescent lamp as comparison. The measurement used in this research is to use the harmonic power analysis instrument. From the result of measurement, it is found that in the experiments on 3 phase 4-wire system when the incandescent lamps are given each phase is balanced, the current in the neutral conductor is 0.08 Amper. While in the second experimental 3 phase 4-wire system when given 2x40 Watt flouresent lamp loads that each phase is balanced, then the current in the neutral conductor becomes excess that is equal to 0.26 Amper. The results of this measurement indicate that the harmonics caused by flouresent lamps are very worrying if the neutral cable carrier used on small-diameter electrical installation network, this could endanger the installation of fire.